General understanding of music perception (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2023)
The fullness of musical perception, the possibility of understanding the means of musical expression, the types of intensity and musical accompaniment are different in each person and have their own characteristics and reasons. Why is music heard by everyone, but not everyone can perceive it? Why some European listeners do not always fully understand Eastern music, and some Eastern listeners do not always understand European Music. Perception is the reflection of things or phenomena in our minds through their direct influence on sensory organs. In psychology, perception is classified into specific qualities such as predisposition, integrity, structural, stability.